Identification of novel sarcomeric modifiers of hypertrophy in hypertrophic cardiomyopathy using the yeast two-hybrid system - Todd, Carol (Stellenbosch : Stellenbosch University, 2013)
Thesis (MScMedSc)--Stellenbosch University, 2013.